Comparative Analysis of the Process of Training Education Managers in Educational Institutions - Askarbek K. Kusainov; Kamchat A. Yessenova; Roza S. Kassymova; Kuanysh S. Moldassan; Ardak M. Sembayeva (European Research Network Vocational Education and Training (VETNET), 2021)
Context: A significant part of future specialists receive only practical skills without formal practical exam situation. In this regard, there is a need to train a manager who can adapt and be ready to carry out his/her activities in a specific profile interaction. The aim of the experimental study was to develop and test the advanced working hypothesis about the possibility of effective formation of readiness for future self-realisation of future education managers. Approach: The work uses mathematical methods for testing the hypothesis of testing the readiness of education managers with verification of competency type. Findings: The novelty of the study is determined by what the authors are considering "the possibility of training a manager in accordance" including not only the standards for the provision of educational services to the population, but also the possibility of introducing world-class training standards. The authors show that the basis for such a development may be the readiness to work in a globalised environment. The dynamics of changes in the indicators of the levels of readiness for professional self-realization of students studying in the control and experimental groups from the first to the fourth year were compiled and recorded. The methodology of vocational training of students for the purpose of their self-realisation during training has been specified. The practical significance of the study is determined by the fact that integration with the global educational environment should be based on international standards for the provision of educational services.  Conclusion: The results of this research can be useful and interesting to international readers, as the parameters of educational and methodological support have been developed and tested, which contains a set of situational exercises to form readiness for professional self-realisation for future education managers. Also, the conducted analysis indicated serious problems with the employment of university graduates both in the Republic of Kazakhstan and in the Republic of Lithuania.